Anthony Reid and the study of the Southeast Asian past - Wade, Geoff; Li, Tana; Reid, Anthony 1939- (Nalanda-Sriwijaya series, 2012)
To celebrate Anthony Reid's numerous and seminal contributions to the field of Southeast Asian history, a group of his colleagues and students has contributed essays for this Festschrift. In addition to introductory essays which provide personal and intellectual histories of Anthony Reid the man, there is a range of original scholarly contributions addressing historical issues which Reid has researched during his career. Divided into sections which examine Southeast Asia in the world, early modern Southeast Asia, and modern Southeast Asia, these works engage with issues ranging from the Age of Commerce and comparative Eurasian history, to nationalism, ethnic hybridity, Islam, technological change, and the Chinese and Arabs in Southeast Asia. The authors include some of the foremost historians of Southeast Asia in our generation.